Neolignan glycosides from Spiraea salicifolia and their inhibitory activity on pro-inflammatory cytokine interleukin-6 production in lipopolysaccharide-stimulated RAW 264.7 cells. Issue 22 (17th November 2019) - Sun, Shiwei; Liu, Yang; Liu, Xiaohong; Zhang, Shuang; Wang, Wei; Wang, Rongrong; Hou, Yuxue; Wang, Wei
Abstract: Phytochemical investigation of the ethanol extract from the roots of Spiraea salicifolia L. (Rosaceae) led to the isolation of one new neolignan glycoside, (7 S, 8 R )-3, 5-dimethoxy-4′, 7-epoxy-8, 5′-neolignan-3′, 4, 9, 9′-tetraol 9- O - α -L-rhamnopyranoside (1 ), along with two known neolignan glycosides, (7 S, 8 R )-3-methoxy-4′, 7-epoxy-8, 5′-neolignan-3′, 4, 9, 9′-tetraol 9- O - α -L-rhamnopyranoside (2 ) and (7 R, 8 S )-dihydrodehydrodiconiferyl alcohol 9′- O - β -d -glucopyranoside (3 ). The structural characterisations of the isolated compounds were elucidated by spectroscopic data and comparison with the literatures reported on the chemical constituents from Juniperus communis var. depressa . All compounds were isolated for the first time from the Spiraea genus. Furthermore, the isolated compounds were subjected to assay inhibitory activity on pro-inflammatory cytokine interleukin-6 production in lipopolysaccharide-stimulated RAW 264.7 cells and all the compounds showed anti-inflammatory effects. Abstract :